PEMBAYARAN UANG PENGGANTI DAN APLIKASINYA DALAM TINDAK PIDANA KORUPSI - Indra Ariska, Dudung (Yustitia, 2018)
Currently, the issue which is becoming a very big problem is the Corruption Crime. Both corruption carried out openly or clandestinely are all crimes that are very detrimental to society and the State. State losses in corruption are one of the elements that must be proven by the Public Prosecutor, especially for the proven state losses. Corruption Crime also recognizes the efforts of the perpetrators to return the corrupt money to the state. The case of returning the results of corruption to the state as a remedy for the Defendant in freeing himself from the snare of corruption charges. Payment of this substitute money should not exceed the amount of money which was corrupted, so it is expected that the lost state finances can be returned. However, it is not easy to get a replacement payment, since the problems that will be found in practice are very diverse in their problems, even if the money from corruption needs to be found, it must be traced in advance.